IMPLEMENTASI PROGRAM BEDAH RUMAH TIDAK LAYAK HUNI BAGI KELUARGA MISKIN DI KECAMATAN PUPUAN KABUPATEN TABANAN - Sidauruk, Putri Sari; Winaya, I Ketut; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2019)
ABSTRACT Uninhabitable home surgical program is one of the public policy implemented in Sub-distric of Pupuan. This study is to get an actual view about implementation of non-habitable home surgical program for poor family. Thisstudies applies qualitative research method in the form of descriptivesurvey, and data was collected by interview, documentation, observation. Indicator that used in this research are (1) policy standards and objectives, (2) resources, (3) characteristic executor agent, (4) dispotition of implementers, (5) communications of implementers, (6) social, economic, political condition. The result of this study indicate implementation of surgical non-habitable home program is still not optimal. Only policy standards objectives, characteristic executor agent and communications of implementers are running well, while the others such resources, dispotition of implementers and social, economic, political condition are still not going well. Keyword :Policy Implementation, Uninhabitable home surgical, Sub-district of Pupuan